Islamic Performance Index and Profitability: Bank Size as a Moderating Variable in Islamic Commercial Banks in Indonesia - Sabrang Gilang Gemilang Gilang; Suci Asmarani (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to examine the impact of the Islamicity Performance Index (IPI) on the profitability of Islamic Commercial Banks in Indonesia, with bank size as a moderating variable. The IPI is measured through several ratios, namely the Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), Directors Employees Welfare Ratio (DEWR), and Islamic Income vs Non-Islamic Income (ISIN). Profitability is calculated using Return on Assets (ROA), while bank size is measured using the natural logarithm of total assets. The research method used was quantitative with multiple linear regression analysis, involving six Islamic Commercial Banks as examples with an observation period from 2019 to 2023. The results showed that EDR had a significant negative effect on ROA, but this effect reversed to positive in larger banks. The variables ZPR, PSR, DEWR, ISIN, and their interaction with bank size have no effect on ROA. These findings emphasize that EDR and ZPR are important indicators of Islamic bank financial performance, where bank size influences the direction and strength of their impact.